Chlamydial cervicitis and urethritis: single dose treatment compared with doxycycline for seven days in community based practises. Issue 2 (April 1996) - Thorpe, E M; Stamm, W E; Hook, E W; Gall, S A; Jones, R B; Henry, K; Whitworth, G; Johnson, R B
Abstract : STUDY GOAL: To compare the efficacy and safety of single 1 g oral azithromycin with doxycycline, 100 mg twice daily for seven days for treatment of uncomplicated urogenital chlamydial infection. STUDY DESIGN: Randomised, unblinded, comparative trial, involving 597 patients demonstrating clinical evidence of genital chlamydia and a positive non-culture assay for Chlamydia trachomatis. RESULTS: Among the azithromycin- and doxycycline-treated patients 61% and 60%, respectively, were asymptomatic within one week after the first dose. At two weeks, these figures increased to 86% and 83%, respectively. Bacteriological eradication, based on a negative assay, occurred in 338 (97%) of 347 azithromycin-treated patients and 161 (99%) of 163 doxycycline-treated patients. CONCLUSION: Treatment of uncomplicated chlamydial cervicitis and urethritis with single 1 g oral azithromycin is equivalent to standard therapy with doxycycline. Drug-related adverse events were approximately twice as common as previously reported for both drugs.